Beyond Cartesian Philosophy of Essentialism, and the Quest for Intercultural Discourse: Some Examples - Molla, Belete (Ethiopian Journal of the Social Sciences and Humanities, 2023)
Rene Descartes is believed to be the founder of modern philosophy that exalts closure, singularity and monologue in the making of philosophical meanings. He sees mankind’s diverse horizons as virtually closed monads; undermines the possibility of openness, mutuality and dialogue. Accordingly, for Descartes, mankind has no common world to refer to, no common vision to live for; the world is essentially uncommunicative and windowless. The purpose of this article is to critically challenge this picture of humanity while trying to identify lessons that need to be critically attended towards forming a world of possibilities in which meaning is discovered rather through the acts of openness, mutuality, and dialogue. I take inspiration from intercultural philosophy that promotes an image of humanity that is an antithesis to the one maintained by Descartes. I will argue that mankind is not only capable of and optimistic to forming a world of better meanings through the revealing power of dialogue, perhaps mankind is a subject endowed with the capacity to dialogically break supposedly unbreakable boundaries. I urge on the need to celebrate the objectivity of an underlying truth of commonness amidst diversities. As will be defended, this last is not a merely speculative attribution of mankind for, indeed, there are concrete historical moments that could offer grounds for meaningful philosophical discernment. While one such example is Ethiopian, others are international which, I believe, could reveal an immense capacity to making the world become converse to and richer in meaning than the mutually isolating effects of Cartesian Either/Or and its world of windowlesseness.